Hercules' sanctuary in the quarter of St Theodore, Pula - Starac, Alka, 1966- (Archaeopress Roman archaeology, 2018)
Dealing with many aspects of the Roman sanctuary erected at the spring in Pula, Croatia, as well as with objects of cult dated to the Hellenistic period, this book provides a hypothetical reconstruction of the Roman sanctuary followed by calculations of construction costs.